Open Access Digital Platforms to Enforce Competition in Contract Farming - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
In 2020, government of India introduced some major policy changes in the Agriculture sector. These changes deal primarily with agricultural marketing. Following these changes, contract farming is now permitted all across India. However, concerns have been raised about monopolistic practices that the sponsors (usually big corporations) in contract farming arrangements could engage in, which would be detrimental to the interests of farmers. Open access digital platforms have the potential to adress some of these concerns by making commodity prices and quality norms publicly available. They could also reduce information asymmetry among contract farming participants and thus create a level-playing field. We propose a platform, similar to existing e-marketplaces that match buyers with sellers, where farmers can express willingness to undertake production of agricultural commodities on contract with pre-specified quantity, quality and price norms and sponsors can easily find willing farmers. Such platforms would have the potential to provide more opportunities for farmers, introduce competition in contract farming space, and reduce information asymmetries, and thus safeguard and advance farmers' interests.
Keywords: 330